Pengaruh Model Cooperative Learning Tipe Make A Match Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Kelas VII di SMPN 2 Kutawaluya Karawang - Siti Nurhasanah; Debibik Nabilatul Fauziah; Neng Ulya (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
The cooperative learning method of the make a match type is a more effective learning model with the growth of student enthusiasm in learning Islamic Religious Education by being actively involved both individually and in groups. This study aims to determine the use of the cooperative learning model of the make a match type in Islamic Religious Education subjects in class VII of SMPN 2 Kutawaluya Karawang, to find out the learning outcomes of students in the subject of Islamic Religious Education of class VII at SMPN 2 Kutawaluya Karawang and to find out whether there is an influence of the cooperative learning model of the make a match type on student learning outcomes in the subject of Islamic Religious Education of class VII at SMPN 2 Kutawaluya Karawang. This study uses a quantitative methodology included in the category of experimental research, data collection through tests in the form of pretests and posttests and data collection with documentation. The subjects taken by the researcher were students of class VII B as an experimental class by applying treatment and students of class VII E as a control class that was not given treatment. The results of the study showed that in the use of the cooperative learning model of the make a match type obtained more effective learning. In addition, student learning outcomes by obtaining a posttest for the experimental class 76.91 and the posttest results for the control class 66.03. Based on the independent sample t-test hypothesis test, there are significant results, namely 0.000 < 0.05 on the posttest results of the experimental class that was treated using the make a match type cooperative model and the results on the control class that was not treated. Furthermore, the results of the N-Gain test were in the experimental class with a total of 44.29% in the quite effective category and the results of the control class N-Gain were 15.92% in the ineffective category. This can be seen that the make and match type cooperative learning model has a fairly effective influence on student learning outcomes in Islamic Religious Education subjects.